2022
DOI: 10.1101/2022.07.23.501268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of pre-existing microbiome and metabolic vulnerabilities to escalation of oxycodone self-administration and identification of a causal role of short-chain fatty acids in addiction-like behaviors

Abstract: The gut brain axis is thought to play a role in behavior and physiological responses through chemical, immunological, and metabolite signaling. Antibiotics, diet, and drugs can alter the transit time of gut contents as well as the makeup of the microbiome. Heterogeneity in genetics and environment are also well-known factors involved in the initiation and perpetuation of substance use disorders. Few viable genetic or biological markers are available to identify individuals who are at risk of escalating opioid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…In recent years the understanding of the microbiome as a regulator of brain and behavior has increased markedly ( Meckel and Kiraly, 2019 ; Rea et al, 2020 ; Lucerne et al, 2021 ). Recent work by our group and others has shown that alterations to the microbiome of rodents can affect cocaine ( Kiraly et al, 2016 ; Lee et al, 2018 ) and opioid reward and reinforcement ( Hofford et al, 2021b ; Simpson et al, 2022 ), can influence tolerance to opioids ( Kang et al, 2017 ; Zhang et al, 2019 ), and can alter cellular and molecular responses to opioids ( Simpson et al, 2020 ; Hofford et al, 2021b ). Previous work from our group measured morphine reward in mice after microbiome knockdown and found that mice with a reduced microbiome displayed reduced morphine place preference at higher doses ( Hofford et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the understanding of the microbiome as a regulator of brain and behavior has increased markedly ( Meckel and Kiraly, 2019 ; Rea et al, 2020 ; Lucerne et al, 2021 ). Recent work by our group and others has shown that alterations to the microbiome of rodents can affect cocaine ( Kiraly et al, 2016 ; Lee et al, 2018 ) and opioid reward and reinforcement ( Hofford et al, 2021b ; Simpson et al, 2022 ), can influence tolerance to opioids ( Kang et al, 2017 ; Zhang et al, 2019 ), and can alter cellular and molecular responses to opioids ( Simpson et al, 2020 ; Hofford et al, 2021b ). Previous work from our group measured morphine reward in mice after microbiome knockdown and found that mice with a reduced microbiome displayed reduced morphine place preference at higher doses ( Hofford et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the understanding of the microbiome as a regulator of brain and behavior has increased markedly [3][4][5] . Recent work by our group and others has shown that alterations to the microbiome of rodents can affect cocaine 6,7 and opioid reward and reinforcement 8,9 , can influence tolerance to opioids 10,11 , and can alter neuronal activation and transcriptional responses to opioids 8,12 . While this work was critical in establishing the role for gut-brain signaling in models of OUD, previous work has relied on transcriptional profiles and indirect measures of opioid reward as readouts for effects of the microbiome on brain and behavior.…”
Section: Introductionmentioning
confidence: 99%